PERFORMANCE OF MATERNAL AND CHILD HEALTH PROGRAM MANAGERS AND FAMILY PLANNING IN THE PROCESS OF PLANNING A HEALTH BUDGET BASED ON SPM (MINIMUM SERVICE STANDARDS) IN THE HEALTH SECTOR AT THE SENGETI HEALTH CENTER - Lesta Andriani; Andy Amir; Dwi Noerjoedianto (International Journal Of Health Science, 2023)
Minimum Service Standards (SPM) are contained in the Regulation of the Minister of Health of the Republic of Indonesia Number 4 of 2019 which regulates the type and quality of basic services required by regional affairs and are entitled to be obtained by everyone at least. The annual target of SPM requires inputs and processes as a performance plan for puskesmas activities within a certain time span. Data on program performance achievements at the Sengeti Health Center for the maternal and child health and family planning Program in 2021 and 2022 are still below target on average. Pemerintah daerah harus menyusun dan menghitung besaran anggaran untuk pemenuhan kewajiban tersebut agar melaksanakan tugas wajib sesuai dengan standar pelayanan minimal. The purpose of this study is to identify the planning and budgeting process of the Kia-Kb program related to the implementation of Minimum Service Standards (SPM) in the health sector at the Sengeti Health Center. This research uses qualitative research methods with a case study approach with 9 informants. Data was collected by conducting in-depth interviews and observations at the Sengeti Health Center from January to March. The results of this research in the aspect of input consisting of human resources, funds, and infrastructure facilities were obtained, namely in quantity and quality according to standards, but training held by the Health Office was only required for program holders. Facilities and infrastructure in the maternal and child health and family planning program are fairly incomplete. Obstacles in terms of funds are often late disbursement of funds. Aspects of the budget planning process have been carried out with 5 stages. Output aspects in the form of RUK and RPK preparation are carried out at the end of each year. The outcome aspect of the Kia-Kb Program has not reached the SPM target where the desired target is 100%.